Mastalgia Assesment and Hormonal Correlations in Patients with Polycystic Ovary Syndrome - Emel Kıyak Çağlayan; Levent Seçkin; Ayşe Yeşim Göçmen; Aylin Okur; Ergin Arslan; Halil İbrahim Serin; Kasım Çağlayan; Yaprak Engin Üstün (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: The aim of this study is the assesment of relationship between mastalgia and hormonal parameters and frequency of mastalgia in polycystic ovary syndrome (PCOS).